THE CONCEPT OF REGIONAL COMPETITIVENESS AND ITS ECONOMIC CONTENT (as an example of Khorezm region)\ (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This thesis examines the concept of regional competitiveness and its economic content from a theoretical perspective, using the case of the Khorezm region. The study evaluates the region’s economic potential, the efficiency of resource utilization, and the key factors determining its competitive advantages. Furthermore, priority directions and practical recommendations aimed at enhancing regional competitiveness are developed.